Niveles de gallinaza en la alimentación de cuyes (Cavia porcellus L.) en la fase de engorde en el cantón Salcedo. - Romero Ramón, Egar Jhon (2013)
This research was executed in the province of Cotopaxi to the North - East of the Salcedo Canton at 1 km from the urban sector via Navas Rumipamba farm Primavera 4 owned by Mr. Miguel Aguilar. The field investigation was 10 weeks. He had objective general to assess levels of manure in Guinea pigs (cavia porcellus l.) feeding in the phase of fattening in the canton Salcedo. The experimental design is the factorial Sex * Levels ken with DBCA Design (block design randomly) with eight treatments each and 3 experimental units, with four replications, where the factors are 4 levels of manure and sex. Results: in total food consumption with females and manure treatment to 10% reported the highest consumption with 1,343.91 g of concentrated. The higher total gain was with treatment with chicken manure to 20% with 1,135.00 g in females. As regards the total conversion treatment with 10% of chicken manure with 1.29 level proved to be more efficient than the rest of the treatments. Treatment with manure 20% with the highest percentage to the channel (79.21%). xv The treatment who showed the net profit realized in treatments 1 (males with 100% Green fodder) and 5 cuyes (females with 100% Green fodder) with a value of 117.35 dollars and a net profit of 3.46 relationship.